2020
DOI: 10.1109/lcsys.2020.2988515
|View full text |Cite
|
Sign up to set email alerts
|

On the Differentiability of Projected Trajectories and the Robust Convergence of Non-Convex Anti-Windup Gradient Flows

Abstract: This paper concerns a new class of discontinuous dynamical systems for constrained optimization. These dynamics are particularly suited to solve nonlinear, non-convex problems in closed-loop with a physical system. Such approaches using feedback controllers that emulate optimization algorithms have recently been proposed for the autonomous optimization of power systems and other infrastructures. In this paper, we consider feedback gradient flows that exploit physical input saturation with the help of anti-wind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The key aspect in (47) is the fact that ∇ Φ is evaluated at P U (u) rather than at u. In Hauswirth et al (2020d) it was shown that trajectories u(t) of (47) converge in the sense that P U (u(t)) converges to the set of KKT points of the optimization problem minimize Φ(u) subject to u ∈ U .…”
Section: Input Saturation Via Projection and Anti-windupmentioning
confidence: 99%
“…The key aspect in (47) is the fact that ∇ Φ is evaluated at P U (u) rather than at u. In Hauswirth et al (2020d) it was shown that trajectories u(t) of (47) converge in the sense that P U (u(t)) converges to the set of KKT points of the optimization problem minimize Φ(u) subject to u ∈ U .…”
Section: Input Saturation Via Projection and Anti-windupmentioning
confidence: 99%
“…This leads to algorithms similar to sequential quadratic programming schemes [49]. Another possibility are anti-windup approximations [30,31] which serve to implement projected dynamical systems as the closed-loop behavior of feedback control loops that are subject to input saturation in feedback-based optimization [10,18,29].…”
Section: Stability Of Projected Gradient Flowsmentioning
confidence: 99%
“…Convergence and stability analysis for regulation of linear time-invariant systems towards the optimal solution of a time-varying convex optimisation problem is studied in [16]. Constraints are included in [17], [18] and [19] extends to non-linear systems and non-convex problems.…”
Section: Introductionmentioning
confidence: 99%